Pengaruh Penggunaan Aplikasi TikTok terhadap Minat Belajar Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar Angkatan 2021 Universitas Trunojoyo Madura - Dessey Nuril Faradiba; Fatimah Azzahra; Agung Setyawan (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
The rapid advancement of digital technology has significantly influenced various aspects of human life, including higher education. One of the most widely used social media platforms among university students is TikTok, which offers entertainment, communication, and educational content. However, excessive use of TikTok may also affect students' learning interest. This study aimed to analyze the influence of TikTok usage on the learning interest of students from the Elementary School Teacher Education (PGSD) Program, Class of 2021, at Universitas Trunojoyo Madura. This research employed a descriptive qualitative approach. Data were collected through an online questionnaire distributed to 51 students selected as research respondents. The collected data were analyzed descriptively to identify students' perceptions regarding the impact of TikTok on their learning interest. The findings revealed that most respondents perceived TikTok as having a significant influence on their learning interest. Twenty-two students reported negative impacts, such as reduced motivation to study, procrastination, poor time management, and decreased concentration due to excessive use of the application. Fourteen respondents stated that TikTok did not affect their learning activities, while fifteen respondents considered the platform beneficial because it provided educational content, current information, and learning motivation. These findings indicate that the influence of TikTok on learning interest depends largely on students' self-control and the way they utilize social media. Therefore, the wise and balanced use of TikTok is essential to maximize its educational benefits while minimizing its negative effects on academic performance.